UNA POLÍTICA PÚBLICA DE LA MUJER CON PERSPECTIVA DE GÉNERO - Obando Salazar, Olga Lucía (Cuadernos de Administración, 2006)
The central issue of this presentation is to review aspects refering to the perspective of Gender in the planning, design, construction, implementation and evaluation of public policies of women, as a local and regional process, inside other wider processes such as Globalism, Governability and Territory. The text is structured in three parts: in the first one are treated some discomforts that are generated in the critical reading of the documents “Women constructors of peace and developments policy” and “Features of policy of fairness of gender for the women of different sectors and ethnic groups from the Valle del Cauca”. These restlessness talk about the implicit and explicit use made in the text of the concepts of Public Policy, Woman and Gender. The second part refers to the role of the agents that participate in the construction, managment and implementation of woman’s public policy. And in a third part the situation of the present development of a woman’s public policy in a departmental level (Valle del Cauca) is resumed.